Propolis supplementation can reduce serum level of interleukin-6, C-reactive protein, and tumor necrosis factor-α: an updated systematic review and dose-response meta-analysis on randomized clinical trials - Ali Gholami; Negar Dinarvand; Mitra Hariri (BMC, 2024)
Abstract Background New evidence suggested that propolis might reduce serum levels of inflammatory mediators; therefore, in this study we aimed to prove the potential effect of propolis on serum levels of interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor-alpha (TNF-α) through conducting a systematic review and meta-analysis. Methods Databases including PubMed, ClinicalTrials.gov, Scopus, Cochrane Library, and ISI Web of Science were searched until October 2023. In the present meta-analysis, we detected the overall effect sizes using extracted standard mean differences (SMD) and the standard deviations (SDs) from both study groups through DerSimonian and Laird method. Exploring the statistical heterogeneity was done through Cochran's Q test and I-squared statistic. Results In total, seventeen and sixteen studies were included in the systematic review and meta-analysis, respectively. The overall estimate indicated that the propolis significantly reduced serum levels of IL-6 (SMD = -3.47, 95% confidence interval (95%CI): -5.1, -1.84; p < 0.001), CRP (SMD= -1.73, 95%CI: -2.82, -0.65; p = 0.002), and TNF-α (SMD= -1.42, 95%CI= -2.15, -0.68; p < 0.001). These results also revealed geographical region and propolis dose were the critical points to get the beneficial effects. Conclusion According to our result, propolis supplementation can decrease serum levels of IL-6, CRP, and TNF-α; therefore, it might be considered as complementary therapy for the treatment of certain chronic diseases.